Accountability of Village Fund Allocation in Efforts to Improve Development in Villages in Pandeglang District (Case Study on Cibaliung Village, Cimanggu Village, and Sukasari Village) - Roheti; Vivi Oktari (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the role of accountability in the management of Village Allocation Funds (ADD) for the 2024 fiscal year in three villages in Pandeglang District—Cibaliung, Cimanggu, and Sukasari—in efforts to enhance village development. The study was conducted using a descriptive qualitative approach through interviews, observations, and analysis of official village documents and other supporting data. The findings indicate that the implementation of accountability in the three villages varies in effectiveness, influenced by the capacity of village officials, transparency mechanisms, and community participation. Sukasari Village shows the highest level of accountability due to strong community involvement and the use of digital information media, while Cibaliung Village is categorized as moderate, and Cimanggu Village faces challenges with documentation and limited budget publication. The use of ADD in Cibaliung and Cimanggu Villages is more focused on infrastructure development, while Sukasari Village has directed its budget toward improving public services and community empowerment. The study concludes that accountability is a determining factor in the success of village development. Recommendations are made for village governments to improve the capacity of officials, expand digital budget publication, and encourage community participation as part of social oversight to strengthen village financial governance sustainably.